Protoariciella uncinata Hartmann-Schröeder, 1962 (Polychaeta, Orbiniidae): a new record for intertidal mussel beds of the Southwestern Atlantic shore affected by sewage effluents - Elias, Rodolfo (2000)
Protoariciella uncinata (Polychaeta, Orbiniidae) is mentioned for the first time in southwestern Atlantic shores, from mytilid mussel beds of Brachidontes rodriguezi of the Mar del Plata area, Argentine. The species was formely described for mytilids banks of the Pacific coast of Chile and Peru. The work also provides information about spatial distribution, relationship with sewage organic enrichment, density and other ecological data.